The Effect of Teacher's Professional Competence on Teacher Creativity in Elementary School - Mastur, Mastur; Zainuddin, Zainuddin (Mimbar Sekolah Dasar, 2023)
This study aims to determine and examine empirical data related to the influence of teacher professional competence on teacher creativity in elementary schools. This research is a correlational study with sample confidence of 90% or an error rate of 10%, the number of samples obtained was 24 people. Data was taken using 2 methods, namely questionnaires and documentation. Testing the instrument validation with expert judgment and then testing the validity and reliability using the Cronbach Alpha formula. The data analysis technique uses simple correlation analysis (product-moment). Test requirements analysis consists of normality test and linearity test. This study's results indicate a positive and significant influence between Teacher Professional Competence and Teacher Creativity, with the correlation of the independent variable with the dependent variable being 1.01 at a significance level of 10%. This means that every unit increase in the teacher's professional competence score will simultaneously affect the increase in the teacher's creativity score.